Analysis Characteristics of Pregnant Mother With Preeclampsia in Agronursing Area - Kurniawati, Dini; Septiyono, Eka Afdi; Juliningrum, Peni Perdani; Rahmawati, Ira (Journal Of Nursing Practice, 2019)
Background: Maternal Mortality Ratio (MMR) is an indicator of health and quality of human resources. One of the causes of MMR is preeclampsia. Preeclampsia is an increase in blood pressure during pregnancy, which it cannot yet be determined. Purpose: Aims of this study are to analyze the characteristics of pregnant women with preeclampsia in seven hospitals in the agriculture area. Methods: Respondents obtained were 441 pregnant women with preeclampsia and analyzed by frequency distribution. Results: The results of the study show that the distribution of patient preeclampsia was most often found at RSU Dr. Abdoer Rahem that is a number of 125 patients (28.3%). The most characteristic mothers with preeclampsia on reproductive age (75.5%), primipara (54.6%), no have a history of the contagious disease (95.9%), no have a history of preeclampsia (83.2%). The most prevalent preeclampsia have a history of preeclampsia. Conclusion: Nurses conduct studies on pregnant women to prevent preeclampsia through a characteristic analysis of pregnant women with preeclampsia.